Sosialisasi Pengenalan Gizi Buruk bagi Anak Usia Dini (Balita) di Posyandu Garuda 04 Kelurahan Harapan Jaya, Bekasi - Suhardoyo Suhardoyo; A.Sudrajat; Roydawaty Bunga Sihol; Dudi Duta Akbar (ARDHI : Jurnal Pengabdian Dalam Negri, 2025)
The purpose of this community service activity is to increase knowledge for mothers at the Garuda 04 Posyandu in Harapan Jaya Bekasi on how to use income to manage a balanced life between the needs of early childhood or toddlers and family needs. The results show that most members of the Garuda 04 Posyandu do not understand properly and correctly how to manage family income properly and correctly from the financial income they earn, such as the difference between needs and wants, budgeting, and the importance of saving and managing the fulfillment of toddler needs for the children they have. The training was conducted in one day with a participatory-educational approach and socialization. This method includes providing materials, group discussions, simulations, and reflections from each individual. The activities showed high active participation from participants and were actively involved in the discussions that were carried out. This socialization provides evidence that an experience-based approach can effectively increase understanding and awareness of the importance of financial management that they are facing.